2022
DOI: 10.3390/metabo12070606
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Regulates the Metabolic Homeostasis of Methamphetamine Dependence

Abstract: Physical exercise is effective in enhancing cognitive function, reducing anxiety and depressive symptoms, reducing cravings, and improving quality of life in methamphetamine (METH) addiction. However, little is known about the effect of exercise on metabolic profiles. We performed LC/MS-based targeted metabolic profiling on serum samples to investigate the metabolic characteristics of METH dependence and find the differences between METH-dependent individuals and nonusers and evaluated the metabolomic profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Nonetheless, the authors claim the application of a multi‐metabolite profiling panel to be of use for investigating training load in runners. This wideband targeted approach was also identified in six additional studies over the past year 25,26,28,40,52,53 …”
Section: Analytical Approaches For Ms‐based Investigations In Ses In ...mentioning
confidence: 92%
See 2 more Smart Citations
“…Nonetheless, the authors claim the application of a multi‐metabolite profiling panel to be of use for investigating training load in runners. This wideband targeted approach was also identified in six additional studies over the past year 25,26,28,40,52,53 …”
Section: Analytical Approaches For Ms‐based Investigations In Ses In ...mentioning
confidence: 92%
“…In 2022, targeted analyses were the most commonly applied approach for MS-based research in SES, with 52 human participant studies published. These experiments were predominantly performed in plasma 6,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] or serum, [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] with other biosamples mediums utilized such as urine, [51][52][53][54][55] fecal matter, 56,57 breath gases, [58][59][60][61][62][63] red blood cells, …”
Section: Targeted Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, this emerging method can be used to identify changes in metabolites affected by addictive drugs [19]. Clinical studies have found that compared with non-drug users, MA abusers have disturbances in serum metabolism, including phenylalanine metabolism, glyoxylate and dicarboxylate metabolism, and alanine, aspartate and glutamate metabolism, which may partially explain the oxidative stress and neuroin ammatory changes induced by MA [31]. Furthermore, metabolomics studies based on magnetic resonance imaging and positron emission tomography suggested that brain volume is affected in MA-dependent individuals, and the major metabolites in brain tissue are abnormally represented, including N-acetylasparate and total creatine [32].…”
Section: Introductionmentioning
confidence: 99%
“…Physical exercise is considered a potential treatment for MA addiction (25)(26)(27). And numerous mechanisms have been proposed to explain why exercise can improve the health of MA-dependent individuals, including the improvement of the nervous system, the improvement of the inhibitory control ability, the recovery of the monoaminergic system, the recovery of the blood-brain barrier, and the remodeling of cortical function (28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%